The impact of sound experiences on the shopping behaviour of children and their parents. Issue 2 (7th April 2015) - Hultén, Bertil M L
Abstract : Purpose: – The purpose of this paper is to examine how the introduction of auditory sensory cues, through a human voice, affect children's and parent's shopping behaviour in a retail grocery setting. In the field of retailing and sensory marketing research, there is a paucity of knowledge on how auditory sensory cues impact on consumers' shopping behaviour. Design/methodology/approach: – The empirical study was a field experiment and entailed direct observation of shoppers of the Swedish grocery retailer ICA. The observations were based on a convenience sample of shopping families assigned to a control group ( n =200) and an experimental group ( n =131). A new innovative Swedish audio story track system was to be tested in a hypermarket containing 13 different stories for children. Findings: – Auditory sensory cues affect children's and parent's shopping behaviour in a significant way. Children are quieter, more relaxed and do not move around and reduce the parental stress behaviour during the shopping process. Research limitations/implications: – The findings demonstrate that auditory sensory cues through human voice have a positive effect on children's and parent's shopping behaviour. It is also obvious that parent's perceived stress is significantly influenced by the children. Practical implications: – The study provides guidelines for grocery retailers who wish to offer children and their parents a more pleasant shopping trip by emphasizing the role of the children. Originality/value: – The research demonstrates that the introduction of auditory sensory cues through human voice in a significant way affect the children's and their parent's shopping behaviour in a retail setting.